Intelligent tutoring system using interactive agent (Echem) / Loo Hoi Keong - Loo , Hoi Keong (2004)
Echem is an intelligent tutoring system using interactive agent. It is a web based learning package that offers the subject chemistry for the SPM candidates. This ITS will fulfill six out of thirteen important topics from the syllabus. The target users are sijil pendidikan malaysia (SPM) candidate. There is an agent named interactive agent that will assist the users throughout the learning session. In the system there consist of learning materials, tutorials' questions and examination models. The aim of the system is to increase the interaction between the system and the users. The process model that is going to be used for this project is waterfall model because it is simple and easy to understand. Besides that, waterfall model i suitable for small scale system. The main development tools for this project are Microsoft visual studio. Net 2003, microsoft SQL server 2000 and other related authoring tools like adobe photoshop or macromedia flash. The main characteristic of the system are user-friendly, attractive interface, easy to navigate and modifiable. The functional requirement for Echem are leaning module, tutorial module, examination module and administrator. For non-functional requirements are user friendliness, interactivity, flexibility and usability.